Development of Learn to Think (LTT) Model Based on Integrated Twin Tower (ITT) to Increase Scientific and Spiritual Creativity of students in the Early Childhood Islamic Education - Pangastuti, Ratna; Fadhillah, Ninik; Prahani, Binar Kurnia (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
The learning model is one way that can increase student creativity. The study aimed to describe and explain the validity of the Integrated Twin Tower (ITT) based Learn To Talk (LTT) learning model. The research method uses Educational Design Research (EDR) to develop a new product. The ITT-based LTT model was developed in order to increase students' creativity. In addition, as follow-up research from the recommendations of previous researchers. The development of this model will be used as teaching material in the classroom. Blended Web Mobile Learning (BWML) is based on the development of ITT-based LTT learning by following John Deway's line of thought. The results of the content validity of the learning model product, which include needs, novelty, theory, planning, and implementation, get an average value of 3.80; 4.00; 4.00; 4.00; and 3.50 with a very valid category. The results of construct validity, the results were obtained with valid categories for all of them. In that way, the ITT-based LTT learning model can be alternative learning to improve students' scientific creative thinking skills.